2011
DOI: 10.1186/1750-1326-6-84
|View full text |Cite
|
Sign up to set email alerts
|

Microglial p38α MAPK is critical for LPS-induced neuron degeneration, through a mechanism involving TNFα

Abstract: BackgroundThe p38α MAPK isoform is a well-established therapeutic target in peripheral inflammatory diseases, but the importance of this kinase in pathological microglial activation and detrimental inflammation in CNS disorders is less well understood. To test the role of the p38α MAPK isoform in microglia-dependent neuron damage, we used primary microglia from wild-type (WT) or p38α MAPK conditional knockout (KO) mice in co-culture with WT cortical neurons, and measured neuron damage after LPS insult.ResultsW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
79
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(89 citation statements)
references
References 51 publications
9
79
1
Order By: Relevance
“…Recent studies have demonstrated that several mechanisms are involved in the pathogenicity of LPS that involve the JNK and P38-MAPK pathways in the production of inflammatory mediators (Xing et al 2011;Wang et al 2012). In the current study, we investigated the neuroprotective activity of an anti-inflammatory compound lupeol against LPS-induced neurotoxicity.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Recent studies have demonstrated that several mechanisms are involved in the pathogenicity of LPS that involve the JNK and P38-MAPK pathways in the production of inflammatory mediators (Xing et al 2011;Wang et al 2012). In the current study, we investigated the neuroprotective activity of an anti-inflammatory compound lupeol against LPS-induced neurotoxicity.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, it has been determined that pharmacological inhibition of p38α-MAPK decreased the levels of the inflammatory cytokines TNF-α and IL-1β, and protected neuronal cells from synaptic protein loss and neurite degeneration (Xing et al 2011;Munoz et al 2007). The JNK signaling cascade acts on AP-1 to promote neuroinflammation and neurodegeneration or interferes with cell deathassociated proteins such as the BCL-2 family of proteins to activate the mitochondrial apoptotic pathway (Bendottil et al 2006;Putcha et al 2003;Tournier et al 2000).…”
Section: Discussionmentioning
confidence: 98%
“…Increased glutamate transmission (and associated excitotoxicity) is thought to play a role in the inflammation-driven neurodegenerative process of MS. In the model system used by Nistico et al, IL-1β secreted by activated microglia was found to suppress GABAergic inhibitory transmission, with limited effects on glutaminergic transmission - in contrast to the impaired hippocampal glutamatergic transmission observed in another EAE model (Xing et al, 2011). However, in both cases the normal balance between excitation and inhibitory inhibition was disrupted, subverting normal synaptic function.…”
Section: Potential Mechanismsmentioning
confidence: 95%
“…MAPK rescued neurons and reduces synaptic protein loss by suppressing LPSinduced TNFα production [30]. Consequently, pharmacological modulation of p38MAPK signalling following LPS stimulation of the microglia is an important strategy in preventing neurodegeneration.…”
Section: Activated Microglia Produce Various Pro-inflammatory Mediatomentioning
confidence: 99%
“…The p38MAPK signalling has been shown to be critical in the expression and activity of pro-inflammatory cytokines in the CNS [30]. In addition, p38 is involved in regulating the production of crucial inflammatory mediators such as COX-2 in macrophages [31].…”
Section: Activated Microglia Produce Various Pro-inflammatory Mediatomentioning
confidence: 99%